2010
DOI: 10.1002/jez.b.21384
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of ENaC expression in the gills and the kidneys of the Japanese black salamander (Hynobius nigrescens Stejneger)

Abstract: A full-length cDNA cloning and tissue distribution of epithelial sodium channel (ENaC) protein were studied during ontogeny by immunohistochemistry in the external gills, and the kidney, pronephros and mesonephros, of the Japanese black salamander, Hynobius nigrescens (Family Hynobiidae; a primitive caudate species). The amino acid sequence of Hynobius ENaCα is 64 and 63% identical to Bufo ENaCα and Rat ENaCα, respectively. In aquatic larva salamander at the digit differentiation stage, Hynobius ENaCα mRNA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In amphibians, ENaC mRNA and protein are expressed in the urinary bladder and ventral skin in addition to the kidney [16,19]. We recently studied the ontogeny of ENaC expression in the external gills and the kidney in a primitive urodele, Hynobius nigrescens [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In amphibians, ENaC mRNA and protein are expressed in the urinary bladder and ventral skin in addition to the kidney [16,19]. We recently studied the ontogeny of ENaC expression in the external gills and the kidney in a primitive urodele, Hynobius nigrescens [19].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, ENaC is important for the evolution of terrestriality during the evolution of early tetrapods, in addition to the acquisition of aldosterone as the most potent sodium-retaining factor in the kidney and colon [19]. Aldosterone is present in tetrapods and in Neoceratodus [20], whereas it is absent in teleosts, elasmobranchs and agnathans [21].…”
Section: Introductionmentioning
confidence: 99%
“…The secondary antibodies used were Alexa Fluor 488‐ and 546‐conjugated goat antirabbit and antiguinea pig Immunoglobulin Gs (IgGs) (Invitrogen). Polyclonal antipeptide antibodies were successfully used as described previously (Uchiyama and Yoshizawa, 2002; Uchiyama et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Using electron microscopy and immunohistochemical techniques, Brunelli and Tripepi (2005) observed that the number of CCs and MRCs in the external gills of larval newts of Triturus italicus increased when these newts were exposed to low pH (pH 4.5) solutions. We also recently reported the cloning and expression of an ENaCα subunit and NHE3 in the Japanese black salamander Hynobius nigrescens (Kumano et al, 2008; Uchiyama et al, 2011). The ENaCα subunit but not NHE3 was observed in the gills and skin of these salamanders.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation